Relationship between Anemia and KEK in Pregnant Women with The Incidence of BBLR in Newborn Babies - Mawarni, Serlis; Wahyuni, Yenni Fitri; Marlina, Marlina; Fitriani, Aida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the relationship between anemia and KEK in pregnant women with the incidence of BBLR in newborns in the Simpang Keuramat Health Center Work Area, North Aceh Regency. This study used an observational analytical approach with a cross-sectional approach method. The results showed that there was a relationship between anemia in pregnant women and the incidence of LBW in newborns (P-0.009), and there was a relationship between KEK in pregnant women and the incidence of BBLR (P-0.000) in the Simpang Keuramat Health Center work area, North Aceh Regency. In conclusion, anemia in pregnant women and chronic energy deficiency (KEK) in pregnant women tend to cause BBLR. Keywords: Anemia, Newborns, BBLR, KEK